The Role of Education in Strengthening Religious Moderation in Indonesia - Aflahah, St; Nisa, Khaerun; Aldeia, AM Saifullah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
Numerous scholarly articles have explored the relationship between education and its role in promoting religious moderation since the concept was introduced in Indonesia. However, only a few articles have been published in journals indexed by Scopus. Concerning Scopus as an accredited journal indexer recognized internationally, this paper's objective was to perform a systematic review of existing literature using the Scopus database from 2019 to 2023 to analyze the significance of education in strengthening religious moderation in Indonesia. The main steps are planning, conducting, and reporting the review. It includes 14 selected articles categorized based on five elements of educational systems: teachers, students, educational objectives, learning management, and educational environments. According to the systematic literature review, education has strengthened religious moderation in Indonesia. It is supported by sufficient teachers' capabilities in teaching religious moderation, students' role as the agents of religious moderation, educational objectives that accommodate religious moderation values, learning managements that use various learning methods and resources, higher thinking order skills, interreligious dialogue, and strategic partnership, and educational environments that provide sufficient learning systems, such as integrating Madrasah Diniyah and Pesantren Universities. However, the implementation still faces challenges requiring more attention from various parties.